2021
DOI: 10.3233/jcb-200024
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma therapy: A promising solution for SARS-CoV-2 outbreak

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has caused more than 18 million confirmed cases and 700000 deaths worldwide after the outbreak in November 2019 (COVID-19). It has been considered as most pathogenic infection under this category. Till date none of the therapeutics or prophylaxis measures have been claimed by any researcher which could cure the patient suffering from the SARS-CoV-2 infection. There is an urgent need for any alternative and effective way of disease management for COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The present report is based on an in silico study of nCoV and associated virus genome sequences analysis to understand the relationship with these respiratory tract infecting viruses. However, the genome sequences of nCoV, SARS-CoV, MERS-CoV was compared with bat-CoV (RaTG13) by Zhou et al where they found similarity 96% with nCoV and 76% with SARS-CoV [6,12]. Additionally, we have compared the all the protein sequences submitted for nCoV on NCBI from all over the world to find the regions where mutation not happened during the spread which is common in viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The present report is based on an in silico study of nCoV and associated virus genome sequences analysis to understand the relationship with these respiratory tract infecting viruses. However, the genome sequences of nCoV, SARS-CoV, MERS-CoV was compared with bat-CoV (RaTG13) by Zhou et al where they found similarity 96% with nCoV and 76% with SARS-CoV [6,12]. Additionally, we have compared the all the protein sequences submitted for nCoV on NCBI from all over the world to find the regions where mutation not happened during the spread which is common in viruses.…”
Section: Introductionmentioning
confidence: 99%